An Immortalized Hepatocyte-Like Cell Line (imHC) Accommodated Complete Viral Lifecycle, Viral Persistence Form, cccDNA and Eventual Spreading of a Clinically-Isolated HBV - Sa-ngiamsuntorn, Khanit (Viruses, 2019)
More than 350 million people worldwide have been persistently infected with the hepatitis B virus (HBV). Chronic HBV infection could advance toward liver cirrhosis and hepatocellular carcinoma. The intervention with prophylactic vaccine and conventional treatment could suppress HBV, but could not completely eradicate it. The major obstacle for investigating curative antiviral drugs are the incompetence of hepatocyte models that should have closely imitated natural human infection. Here, we demonstrated that an immortalized hepatocyte-like cell line (imHC) could accommodate for over 30 days the entire life cycle of HBV prepared from either established cultured cells or clinically-derived fresh isolates. Normally, imHCs had intact interferon signaling with anti-viral action. Infected imHCs responded to treatments with direct-acting antiviral drugs (DAAs) and interferons (IFNs) by diminishing HBV DNA, the covalently closed circular DNA (cccDNA) surface antigen of HBV (HBsAg, aka the Australia antigen) and the hepatitis B viral protein (HBeAg). Notably, we could observe and quantify HBV spreading from infected cells to naïve cells using an imHC co-culture model. In summary, this study constructed a convenient HBV culture model that allows the screening for novel anti-HBV agents with versatile targets, either HBV entry, replication or cccDNA formation. Combinations of agents aiming at different targets should achieve a complete HBV eradication.